THE SITUATION OF ISLAM DURING THE SOVIET GOVERNMENT AND THE REPRESSION OF PRIESTS (TAMADDUN NURI JURNALI, 2024)
The article analyzes the information related to the Soviet government's attitude to religion and its violent policy and repression of religious people from a historical perspective based on reliable sources.